Effects of Coots on duck densities in Saskatchewan parkland - Nudds, Thomas D (Wildfowl, 1981)
The hypothesis that high nesting densities of American Coots Fulica americana might impair breeding duck productivity by suppressing duck population densities was investigated using 26 years of duck and Coot census data and pond abundance data collected at Redvers, Saskatchewan. Using partial correlation to hold environmental variation and effects of interactions with other species constant, each duck species' density was correlated with Coot density in both the nesting and brood-rearing periods. No patterns emerged which were consistent with the hypothesis that Coots detrimentally affect breeding duck densities.